Respon Pertumbuhan dan Produksi Tanaman Terung (Solanum melongena L.) pada Komposisi Media Tanam dan Dosis POC Sampah Dapur Berbeda - Turohmah, Nur Ulfa; Junaidi, Junaidi; Supandji, Supandji; Hadiyanti, Nugraheni (Jurnal Ilmiah Pertanian Nasional, 2023)
Eggplant (Solanum melongena L.) is a favorable vegetable with high economic value. Its production is increased by using various growing media and liquid organic fertilizers (LOF) from household waste to produce organic products. This research aimed to study the interaction effect of the composition of the growing media and the dose of kitchen waste LOF on the growth and yield of eggplant. The experiment used a 3 x 3 factorial Completely Randomized Design (CRD) with three repetitions. The first factor was the composition of planting medium (M) consisting of 3 levels, namely: M1 (soil : cow manure), M2 (soil : cow manure : sand), and M3 (soil : cow manure : burned husk). The second factor was the dose of kitchen waste LOF (D) consisting of 3 levels, namely: D1 (0 cc/plant), D2 (10 cc/ plant), and D3 (20 cc/plant). The variables observed were plant height (cm), number of leaves (strands), stem diameter (mm), leaf area (cm2), number of branches, number of flowers (buds), and fruit production. The results of the observations were analyzed using Analysis of Variance (ANOVA). Once the results were significantly different, it would be continued with the Least Significant Difference (LSD) test at the 5% level. The results showed a significant interaction between the composition of the growing media and the dose of kitchen waste LOF on plant height at nine weeks after planting (WAP). Eggplant plant height at 3 WAP on the treatment of different planting media compositions had a significant effect, with leaf area at seven WAP, stem diameter at nine WAP, and number of branches at fourteen WAP. Treatment of kitchen waste LOF doses significantly affected the number of leaves and stem diameter of eggplant plants aged nine WAP.Â Terung (Solanum melongena L.) salah satu sayuran yang digemari masyarakat dan bernilai ekonomis cukup tinggi. Produksi terung ditingkatkan menggunakan media tanam beragam dan pupuk organik cair untuk menghasilkan produk organik. Tujuan dari penelitian adalah mempelajari pengaruh interaksi komposisi media tanam dan dosis POC sampah dapur terhadap pertumbuhan dan hasil tanaman terung. Percobaan menggunakan Rancangan Acak Lengkap (RAL) 2 faktor dengan pengulangan 3 kali. Faktor pertama adalah komposisi media tanam (M) terdiri atas 3 taraf, yaitu: tanah : pupuk kandang (M1); tanah : pupuk kandang : pasir (M2); dan tanah : pupuk kandang: arang sekam (M3). Faktor kedua adalah dosis POC sampah dapur (D) terdiri atas 3 taraf, yaitu: 0 cc/tan (D1), 10 cc/tan (D2) dan 20 cc/tan (D3). Variabel pengamatan adalah tinggi tanaman (cm), jumlah daun (helai), diameter batang (mm), luas daun (cm2 ), jumlah cabang, jumlah bunga (kuncup), dan produksi buah. Data pengamatan dianalisis menggunakan Analysis of Variance (ANOVA), dan apabila hasil berbeda nyata dilanjutkan uji beda nyata terkecil (BNT) taraf 5%. Hasil penelitian adalah terdapat interaksi yang nyata antara perlakuan komposisi media tanam dan dosis POC sampah dapur terhadap tinggi tanaman umur 9 MST. Tinggi tanaman terung umur 3 MST pada perlakuan komposisi media tanam yang berbeda memberikan pengaruh nyata, luas daun umur 7 MST, diameter batang umur 9 MST, dan jumlah cabang umur 14 MST. Perlakuan dosis POC sampah dapur menunjukkan pengaruh nyata terhadap jumlah daun, dan diameter batang tanaman terung umur 9 MST.